Firm growth, exporting and information communication technology (ICT) in Southern Africa - Rethabile Masenyetse; Malefu Manamathela (Journal of Innovation and Entrepreneurship, 2023)
This paper examines the key determinants of firm growth in three Southern African countries of Eswatini, Lesotho and Namibia and assesses whether exporting activity and use of information communication technology play any role in growth of the firms. The paper uses data collected by the World Bank through enterprise surveys during the period 2014-2016. Employing the ordinary least squares, the results show that firm growth is determined by size of the firm, age, use of information communication technology, exporting activities, foreign ownership and the legal form of the firm. The result is robust even when controlling for industry and country differences. Overall, the results support industrial policy geared towards small firms through rolling out information communication technology infrastructure and promoting access to exporting markets.
Keywords: F140; L25; O31; 650; Exporting; Firm growth; Technology